(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The research aimed to study the attitudes of young people towards artificial intelligence programs in confronting their psychological and social problems. To achieve this goal, the descriptive analytical approach was used, along with the social survey method by sample. A sample of (355) male and female students from the Department of Sociology at Damascus University was selected. The attitude scale was used, which was prepared by the researcher. After collecting and analyzing the data on the (SPSS) program and using appropriate statistical methods, a set of results was reached, the most important of which are: The attitudes of the research sample members towards artificial intelligence programs to solve their psychological and social problems were positive and tended towards acceptance. The reasons behind this were varied, including: positive reinforcement and continuous praise, supporting confidence in actions, confidentiality and lack of feeling of social stigma, permanent availability and personalization of responses. The results also showed that females are more inclined to use the programs compared to males, and first-year students are the most positively inclined towards these programs, and there is no effect of family size. At the end of the research, a set of proposals were presented that would raise the level of awareness of using these programs and dealing with them properly.